Duration of oestrogen exposure does not affect reproductive outcome in artificial cycles: a retrospective analysis of more than 7000 hormonal replacement therapy cycles for an embryo transfer - Rodríguez-Varela, Cristina; Salvaleda-Mateu, Maria; Labarta, Elena (Frontiers in Endocrinology, 2023)
Optimal duration of oestrogen exposure before an embryo transfer in artificial cycles has not been defined yet, as its correlation with reproductive outcome remains controversial. The length of oestrogen treatment before starting luteal phase support varies significantly among patients. In this study, we will conduct a retrospective analysis of a huge database of our own clinical results in artificial cycles in the past five years. The aim of this study would be to assess the effect of the length of estrogen exposure on reproductive outcome and to evaluate if there is any optimal duration of estrogen exposure in order to maximize success rates.